Multifunctional conducting molecular materials - Saito, G. 1945- (RSC Pub., 2007)
The use of conducting molecular materials is a rapidly developing, multidisciplinary field of research, offering a wide variety of possibilities for the future. It is of particular relevance to nano fabrication and technology because it offers high density, small size integrated and multifunctional properties that can be fabricated under mild conditions. Multifunctional Conducting Molecular Materials covers a wide range of topics including: molecular conductors and superconductors; design and synthesis of functional molecular materials; organic/inorganic hybrids and photoinduced phenomena; fullerenes, nanotubes and other related nano materials. The book concludes with a look at integration and functionalities of molecular materials such as organic field effect transistors (OFET). This high level book is ideal for researchers in both industry and academia who are interested in this new and exciting field.
Proceedings of the symposium Science and Engineering of the Future with Multifunctional Conducting Molecular Materials held at the 2005 International Chemical Congress of Pacific Basin Societies (Pacifichem 2005) held in Honolulu, Hawaii, USA on 15-17 Dec. 2005 - t.p. verso.
Keywords: Molecules -- Congresses.; Organic conductors -- Congresses.; Inorganic compounds -- Congresses.; Nanostructured materials -- Congresses.; elektronické knihy; electronic books